PENDAMPINGAN MANAJEMEN USAHA PADA UKM SEPATU BERSIH DI MALANG - Siti Zubaidah; Masiyah Kholmi (Universitas Muhammadiyah Malang, 2020)
This service was carried out in the clean shoe business group. The purpose of this service is to form / develop a group of people as prospective entrepreneurs who are economically independent with a specific target to be achieved is to provide assistance in business management, especially in the bookkeeping and sales system of UKM Clean Shoes in Malang. The partner in this service is UKM